Nove smernice pri oživljanju otroka - Vidmar, Ivan (Medicinski razgledi, 2002)
The latest guidelines in paediatric resuscitation are dealing with the recognition of the cardiac arrest, cardiac massage of infants, treatment of a complete obstruction of the airway, checking of the tracheal tube position, second dose of epinephrine and with antiarhytmic drugs.
Keywords: Kardiopulmonalno oživljanje; Resuscitation Orders; Resuscitation; Oživljanje; Oživljanje, navodila; Heart Massage; Cardiopulmonary Resuscitation; Srce, masaža; baby; Dojenček; Infant; Child; Otrok; urgentna medicina; reanimacija; otroci; postopki